Class 10th-Quadratic Equation- Exercise 4.3.Full notes
(i) 2x2-7x+3=0
(ii) 2x2+x-4=0
(iii)4x2+4√3x+3=0
(iv) 2x2+x+4=0
Ans. (i) 2x2-7x+3=0
First we divide equation by 2 to make co-efficient of x2 equal to 1,
x2-(7/2)x+3/2=0
Divide middle term of the equation by 2x, we get
(7/2)x*(1/2x)=7/4
Add and subtract square of 7/4 from the equation
x2-(7/2)x+3/2=0
x2-(7/2)x+3/2+(7/4)2-(7/4)2=0
x2+(7/4)2-7/2
x+3/2+(-7/4)2=0
{(a-b)2=a2+b2-2ab}
(x-7/4)2-(24-49)/16=0
(x-7/4)2=(49-24)/16
Taking Square root on both sides,
x-7/4= 士5/4
X=5/4+7/4=12/4=3
or
x=-5/4+7/4=2/4=1/2
Therefore, x=1/2 or 3
(ii) 2x2+x-4=0
First we divide equation by 2 to make co-efficient of x2 equal to 1,
x2+x/2-2=0
Divide middle term of the equation by 2x, we get
x/2*1/2x=1/4
Add and subtract square of 1/4 from the equation
x2+x/2-2=0
x2-x/2-2+(1/4)2-(1/4)2=0
x2+x/2+(1/4)2-2-(1/16)=0
{(a+b)2=a2+b2+2ab}
(x+1/4)2-(33/16)=0
(x+1/4)2=33/16
Taking square root on the both sides,
⇒ x+1/4=士√33/4
x=√33/4-1/4=(√33-1)/4
and x= (-√33/4)-1/4 =(-√33-1)/4
Therefore, x=(√33-1)/4 , or (-√33-1)/4
(iii)4x2+4√3x+3=0
Dividing the equation by “4”
x2+√3x +3/4=0
Now According to
the procedure of completing the square,
x2+√3x +3/4 +(√3/2)2-(√3/2)2 =0
x2+(√3/2)2+√3x+3/4-3/4 =0
{(a+b)2=a2+b2+2ab}
(x+√3/2)2=0
(x+√3/2)(x+√3/2)=0
Taking square root on the both sides,
(x+√3/2)=0 , (x+√3/2)=0
x=-√3/2 , x=-√3/2
(iv) 2x2+x+4=0
Dividing the equation by “2”
x2+x/2+2=0
Now According to
the procedure of completing the square,
x2+x/2+2
+(1/4)2-(1/4)2 =0
x2+(1/4)2+x/2+2-(1/4)2 =0
{(a+b)2=a2+b2+2ab}
(x+1/4)2+2-(1/16)=0
(x+1/4)2=(1/16)-2
=(1-32)/16
Taking square root on both sides. Right hand side does not exist because
square root of negative number does not exist.
Therefore, there is no solution for Quadratic Equation 2x2+x+4=0.
2. Find the roots
of the following Quadratic Equations by applying quadratic formula.
(i) 2x2-7x+3=0
(ii) 2x2+x-4=0
(iii)4x2+4√3x+3=0
(iv) 2x2+x+4=0
Ans.
(i) 2x2-7x+3=0
Comparing
quadratic equation 2x2-7x+3=0 with general form ax2+bx+c=0
, we get a=2,b=-7 and c=3
Putting these
values in quadratic formula
⇒x= [-b 士√b2-4ac]/ 2a
⇒x= [7 士√(-7)2-4*2*3)]/ 2*2
⇒x= [7 士√(49-24)]/ 4
⇒x= (7 士√25)/4
⇒x= (7 士5)/4
⇒x= (7+5)/4 or (7-5)/4
⇒ x = 3 or ½
(ii) 2x2+x-4=0
Comparing
quadratic equation 2x2+x-4=0 with general form ax2+bx+c=0
, we get a=2,b=1 and c=-4
Putting these
values in quadratic formula
⇒x= [-b 士√b2-4ac]/ 2a
⇒x= [-1 士√(1)2-4*2*(-4))]/ 2*2
⇒x= (-1 士√33)/4
⇒x= (-1 +√33)/4 or x= (-1-√33)/4
(iii) 4x2+4√3x+3=0
Comparing
quadratic equation 4x2+4√3x+3=0 with
general form ax2+bx+c=0, we get a=4,b=4√3 and
c=3
Putting these
values in quadratic formula
⇒x= [-b 士√b2-4ac]/ 2a
⇒x= [4√3 士√(4√3)2-4*4*3)]/ 2*4
⇒x= [4√3 士√(0)]/ 8
⇒x= -4√3)/8
⇒x= -√3/2
⇒x= -√3/2 , -√3/2
A quadratic equation has two roots. Here, both the roots are equal.
(iv) 2x2+x+4=0
Comparing
quadratic equation 2x2+x+4=0 with general form ax2+bx+c=0
, we get a=2,b=1 and c=4
Putting these values
in quadratic formula
⇒x= [-b 士√b2-4*a*c]/ 2*a
⇒x= [-1 士√(1)2-4*2*4)]/ 2*2
⇒x= [-1 士√(-31)]/ 4
But, the square root of negative number is not defined.
Therefore,
Quadratic equation 2x2+x+4=0 has no solution.
3. Find the roots of the following equations:-
(i) (x-1)/x=3, x
is not equal to 0
(ii) 1/(x+4)-
1/(x-7) =11/30, x is not equal to -4 and 7
Ans. (i) x-1/x=3,
x is not equal to 0
⇒ (x2 -1)/x=3
⇒ (x2 -1)=3x
⇒ x2-3x-1=0
Comparing quadratic equation x2-3x-1=0 with general form ax2+bx+c=0 , we get a=1,b=-3 and c=-1.
Putting these
values in quadratic formula
⇒x= [-b 士√b2-4ac]/ 2a
⇒x= [3士√(3)2-4*1*(-1))]/ 2*1
⇒x= [3 士√(13)]/2
⇒x= (3 士√13)/2
⇒x= (3 +√13)/2 or (3 -√13)/2
Hence, proved.
(ii) 1/(x+4)-
1/(x-7) =11/30, x is not equal to -4 and 7
1/(x+4)-
1/(x-7) =11/30, x is not equal to -4 and 7
⇒ (x-7)-(x+4)/(x-4)(x-7) =11/30
[LCM]
⇒-11/(x-4)(x-7) =11/30
⇒ -30=x2 -7x+4x-28
⇒ x2 -3x+2=0
Comparing
quadratic equation x2-3x+2=0 with general form ax2+bx+c=0
, we get a=1,b=-3 and c=2.
Putting these
values in quadratic formula
⇒x= [-b 士√(b2-4ac)]/ 2a
⇒x= [3士√(3)2-4*1*(2))]/ 2*1
⇒x= [3 士√(1)]/2
⇒x= (3 +√1)/2 or (3 -√1)/2
⇒ x=2,1
Hence, proved.
4. The sum of
reciprocals of Rehman’s ages (in years) 3 years ago and 5 years from now is
1/3. Find his present age.
Ans. Let present
age of Rehman = x yrs.
3 years Ago, Age
of Rehman= (x-3) years
After 3 years , Age of Rehman= (x+5) years
Acc. To the given condition:-
1/(x-3)+1/(x+5) =1/3
⇒ [(x+5)+(x-3)]/[(x-3)(x+5)]=1/3
⇒ 3(2x+2)=(x-3)(x+5)
⇒ 6x+6= x2-3x+5x-15
⇒ x2-4x-15-6=0
⇒ x2-4x-21=0
Comparing
quadratic equation x2-4x-21=0 with general form ax2+bx+c=0
, we get a=1,b=-4 and c=-21.
Putting these
values in quadratic formula
⇒x= [-b 士√(b2-4ac)]/ 2a
⇒x= [4士√(4)2-4*1*(-21))]/ 2*1
⇒x= [4士√(16+84)]/2
⇒x= [4士√(100)]/2
⇒x= (4 +10)/2 , (4 -10)/2
⇒ x=7,-3
Age cannot be negative, so we discard x=-3
Therefore, present age of Rehman is 7 years
5. In a class
test, the sum of Shefali’s marks in Mathematics and English is 30. Had she got
2 marks more in Mathematics and 3 marks less in English, the product of their
marks would have been 210. Find her marks in the two subjects.
Ans:Let Shefali’s marks in Mathematics = x
Let Shefali’s marks in English = 30 − x
If, she had got 2 marks more in Mathematics, than her marks would be
= x + 2
If, she had got 3 marks less in English, then her marks in English would be
= 30 – x − 3 = 27 − x
Acc. to given condition:-
(x+2)(27-x)=210
⇒ 27x-x2+54-2x=210
⇒ x2-25x+156=0
Comparing
quadratic equation x2-25x+156=0 with general form ax2+bx+c=0
, we get a=1,b=-25 and c=156.
Putting these
values in quadratic formula
⇒x= [-b 士√(b2-4ac)]/ 2a
⇒x= [25士√(25)2-4*1*156]/ 2*1
⇒x= [25士√(625-624)]/2
⇒x= [25士√(1)]/2
⇒x= (25+1)/2 , (25 -1)/2
⇒ x= 13 or 12.
Therefore, Shefali’s marks in Mathematics = 13 or 12
Shefali’s marks in English = 30 – x = 30 – 13 =
17
Or Shefali’s marks in English = 30 – x = 30 – 12 =
18
Therefore, her marks in Mathematics and English are (13, 17) or (12, 1)
6. The diagonal of
a rectangular field is 60 metres more than the shorter side. If, the longer
side is 30 metres more than the shorter side, find the sides of the field.
Ans. Let shorter side of rectangle =x metres
Let diagonal of rectangle = (x + 60) metres
Let longer side of rectangle = (x + 30) metres
Acc. to Pythagoras theorem,
(x+60)2=(x+30)2+x2
⇒ x2+3600+120x=x2+900+60x+x2
⇒ x2-60x-2700=0
Comparing
quadratic equation x2-60x-2700=0 with general form ax2+bx+c=0
, we get a=1,b=-60 and c=-2700.
Putting these
values in quadratic formula
⇒x= [-b 士√(b2-4ac)]/ 2a
⇒x= [60士√(-60)2-4*1*(-2700)]/ 2*1
⇒x= [60士√(3600+10800)]/2
⇒x= [60士120]/2
⇒x= (60+120)/2 , (60-120)/2
⇒ x= 90 ,-30
We ignore -30. Since length
cannot be in negative.
Therefore, x=90 which
means length of shorter side = 90 meters
And length of longer side=
x+30 =90+30=120 metres
Therefore, length of sides are 90 and 120 metres.
7. The difference
of squares of two numbers is 180. The square of the smaller number is 8 times
the larger number. Find the two numbers.
Ans. Let smaller number =x and
let larger number =y
Acc. to
condition:-
y2-x2=180…….(1)
Also, we are given that square of smaller number is 8 times the larger
number.
x2 = 8y….(2)
Putting equation (2) in (1), we get
y2-(8y)=180
⇒ y2-8y-180=0
Comparing
quadratic equation y2-8y-180=0 with
general form ax2+bx+c=0 , we get a=1,b=-8 and c=-180.
Putting these
values in quadratic formula
⇒x= [-b 士√(b2-4ac)]/ 2a
⇒y= [8士√(-8)2-4*1*(-180)]/ 2*1
⇒y= [8士√(64+720)]/2
⇒y= [8士√(784)]/2
⇒y= (8+28)/2 , (8-28)/2
⇒ y=18 or 10
Using equation (2) to find smaller number.
⇒ x2=8y =8*18=144
⇒ x = ±12
And,
x2=8y =8*(-10)=144 {No real solution for x}
Therefore, two number are (12,18) (-12,18)
8. A train travels
360 km at a uniform speed. If, the speed had been 5 km/hr more, it would have
taken 1 hour less for the same journey. Find the speed of the train.
Ans. Let the speed of
the train =x km/hr
If, speed had been 5 km/hr more, train would have taken 1 hr less.
Acc. to this condition
360/x=360/(x+5)=1
⇒ 360[(1/x)-1/(x+5)] =1
⇒ 360 [(x+5)-x]/x(x+5)=1
⇒ 360*5 = ⇒ x2 +5x
⇒ x2 +5x-1800=0
Comparing
quadratic equation x2+5x-1800=0. x with general form ax2+bx+c=0
, we get a=1,b=5 and c=-1800.
Putting these
values in quadratic formula
⇒x= [-b 士√(b2-4ac)]/ 2a
⇒x = [-5士√(5)2-4*1*(-1800)]/ 2*1
⇒x = [-5士√(25+7200)]/2
⇒x = [-5士√(7225)]/2
⇒x = [-5士85]/2
⇒x= (-5+85)/2 , (-5-85)/2
⇒ x=40 , -45
Since speed of train cannot be in negative. Therefore, we discard x= -45
Therefore, speed of train =40 km/hr
9. Two water taps
together can fill a tank in 75/8 hours. The tap of larger diameter takes 10
hours less than the smaller one to fill the tank separately. Find the time in
which each tap can separately fill the tank.
Ans. Let time taken by
tap of smaller diameter to fill the tank = x hours
Let time taken by tap of larger diameter to fill the tank = (x-10) hours
It means that tap of smaller diameter fills (1/x)th part of
tank in 1 hour…..(1)
And, tap of larger diameter fills (1/x-10)th part of tank
in 1 hour …….(2)
When two taps are used together, they fill tank in 75/8 hours.
In 1 hour, they fill (8/75)th part of tank 1/(75/8)=
8/75 ……..(3)
From (1), (2) and (3),
(1/x+1)/(x-10) =8/75
⇒ (x-10+x)/ x(x-10) = 8/75
⇒ 75 (2x − 10) = 8(x2 -10x)
⇒ 150x – 750 =8x2 -80x
⇒ 8x2 -80x-150x+750=0
⇒ 4x2 -115x+375=0
Comparing
quadratic equation 4x2-115x+375=0 with
general form ax2+bx+c=0 ,we get a=4,b=-115 and c=-375.
Putting these
values in quadratic formula
⇒x= [-b 士√(b2-4ac)]/ 2a
⇒x = [115士√(-115)2-4*3*(375)]/ 2*4
⇒x = [115士√(13225-6000)]/8
⇒x = [115士√(7225)]/8
⇒x = [115士85]/8
⇒x= (115+85)/8 , (115-85)/8
⇒ x=25, 3.75
Time taken by larger tap = x-10 =3.75 -10= -6.25 hours
Time cannot be in negative. Therefore , we ignore this value.
Time taken by larger tap= x-10=25-10= 15 hours
Therefore, time taken by larger tap is 15 hour and time taken by smaller
tap is 25 hours.
10. An express
train takes 1 hour less than a passenger train to travel 132 km between Mysore
and Bangalore (without taking into consideration the time they stop at intermediate
stations). If, the average speed of the express train is 11 km/h more than that
of the passenger train, find the average speed of two trains.
Ans. Let average speed
of passenger train = x km/hr
Let average speed of express train = (x+11) km/hr
Time taken by passenger train to cover 132 km= (132/x ) hours
Time taken by express train to cover 132 km =[132/(x+11)] hours
Acc. to the given condition,
132/x=[132/(x+11)]+1
⇒ 132 [1/x - 1/(x+11)] =1
⇒ 132[ (x+11-x)/ x(x+11)] =1
⇒ 132 *11=x(x+11)
⇒1452 = x2+11x
⇒ x2+11x-1452=0
Comparing
quadratic equation x2+11x-1452=0 with
general form ax2+bx+c=0 ,we get a=1,b=11 and c=-1452.
Putting these
values in quadratic formula
⇒x= [-b 士√(b2-4ac)]/ 2a
⇒x = [-11士√(11)2-4*1*(-1452)]/ 2*1
⇒x = [-11士√(121+5808)]/2
⇒x = [-11士√(5929)]/2
⇒x = [-11士77]/2
⇒x= (-11+77)/2 , (-5-77)/2
⇒x= 33,-44
As speed cannot be in negative. Therefore, speed of passenger train =33
km/hr
And, speed of express train = x+11 =33 +11 = 44 km/hr
11. Sum of areas of two squares is 468 m2. If, the difference of their perimeters is 24 metres, find the sides of the two squares.
Ans. Let perimeter of
first square = x metres
Let perimeter of
second square = (x+24) metres
Length of side of first square= x/4 metres
{ Perimeter of square = 4* length of side}
Length of side of first square = (x+24)/4 metres
Area of first square= side * side = x/4* x/4 = x2/16 m2
Area of second square = [(x+24)/4]2
Acc. to given condition:-
x2/16 + [(x+24)/4]2= 0
⇒ x2/16 + (x2+576+48x)/16 = 468
⇒ (x2+ x2+576+48x)/16 = 468
⇒2x2+576+48x=468*16
⇒ 2x2+48x+576=7488
⇒ 2x2+48x-6912=0
⇒ x2+24x-3456=0
Comparing
quadratic equation x2+24x-3456=0 with
general form ax2+bx+c=0 ,we get a=1,b=24 and c=-3456.
Putting these
values in quadratic formula
⇒x= [-b 士√(b2-4ac)]/ 2a
⇒x = [-24士√(24)2-4*1*(-3456)]/ 2*1
⇒x = [-24士√(576+13824)]/2
⇒x = [-24士√(14400)]/2
⇒x = [-24士120]/2
⇒x= (-24+120)/2 , (-24-120)/2
⇒ x=48 or -72
Perimeter of square cannot be in negative. Therefore, we discard x=-72.
Therefore, perimeter of first square= 48 metres
And, perimeter of second square = x+24 = 48 +24 = 72 metres
⇒ Side of first square =
perimeter / 4 =48/4 =12 m
And , side of second square
Comments
Post a Comment